Impact of embryo transfer strategies on children health outcomes: a retrospective national cohort study in Taiwan - Chang, Chih-Ting; Weng, Shih-Feng; Chuang, Hui-Yu; Hsu, Chia-Yi; Tsai, Eing-Mei (Frontiers in Endocrinology, 2025)
ObjectiveTo investigate the impact of different assisted reproductive technology (ART) embryo transfer strategies on neonatal and early childhood health outcomes, focusing on fresh versus frozen transfers and cleavage versus blastocyst stages.DesignRetrospective cohort study analyzing data from Taiwan’s national assisted reproduction database (2013–2017).MethodsThe study included 10,803 ART-conceived singleton births and 894,615 naturally conceived singletons. ART groups were categorized by embryo transfer type: fresh cleavage stage, fresh blastocyst, frozen cleavage stage, and frozen blastocyst. Maternal, paternal, and perinatal outcomes were adjusted using inverse probability of treatment weighting (IPTW). Outcomes included major and minor diseases in offspring, such as ADHD, developmental delays, atopic dermatitis, and respiratory diseases.ResultsART-conceived children had higher rates of major and minor health conditions compared to naturally conceived peers, particularly preterm birth, ADHD, and developmental delay. No significant differences were observed in major disease incidence between frozen and fresh transfers or cleavage and blastocyst stages. The elevated risks in ART-conceived children may reflect the influence of underlying parental infertility rather than ART procedures alone.ConclusionWhile ART is linked to increased risks of certain adverse health outcomes, the choice between embryo transfer strategies has minimal impact on neonatal or early childhood health. These findings underscore the need to optimize ART protocols and perinatal care while addressing the role of parental infertility in shaping offspring health.